Zaharuddin Sets His Sights Beyond The Ordinary - New Straits Times, (2008)
When Zaharuddin Saidon took over the helm of TH Properties Sdn Bhd (THP) earlier this year, he didn't just take the reigns of a development company. He assumed the driver s seat of one of the country s largest most ambitious ventures.